Correction: Psychological impacts from COVID-19 among university students: Risk factors across seven states in the United States - Browning, Matthew H. E. M.; Larson, Lincoln R.; Sharaievska, Iryna; Rigolon, Alessandro; McAnirlin, Olivia; Mullenbach, Lauren; Cloutier, Scott; Vu, Tue M.; Thomsen, Jennifer; Reigner, Nathan; Metcalf, Elizabeth Covelli; D’Antonio, Ashley; et al. (PloS one, 2022)
Given the dominance of the COVID-19 pandemic in the news, it could have been expected that younger "always-on" students were exposed to greater amounts of risk-elevating messages, which could have led to anxiety and poor mental health [16,75]. Since our data suggest the opposite, further investigation into social media use and reactions among younger and older students is called upon to understand why older students were at greater risk of psychological impacts. Results of mixed-effects binary logistic regression modelling likelihood of risk factors predicting assignment to high COVID-19 psychological impact profile for students in seven United States universities (N = 2,140) a. https://doi.org/10.1371/journal.pone.0273938.t001 Supporting information S3 Table. Results of binomial logistic regression modelling likelihood of risk factors predicting high versus low/moderate levels of COVID-19 psychological impact for students at North Carolina State University, where a representative sample was collected (N = 1,312). https://doi.org/10.1371/journal.pone.0273938.s001 (DOCX) Acknowledgments The authors apologize for the unintentional mischaracterization of younger adults being at higher risk of psychological impacts from COVID-19.